PENGARUH IKLIM ORGANISASI, KEPEMIMPINAN TRANSFORMASIONAL DAN SELF EFFICACY TERHADAP PERILAKU KERJA INOVATIF - DIAN TRIKUSUMA WARDHANI; YUPITER GULO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The purpose of this research is to examine the relationship the influence of innovative work behavior base on the three dimension as work of organizational climate, transformational leadership, and self efficacy of islamic bank in Bekasi. The methods which is used in th research is descriptive and casuality respondents involved in this study as many as 53 people. The study used sample saturated sampling. The data collection is done by spreading questionnaire. And the method for the data analysis in this research is regression which are and multiple regression. The result of this research is work of organizational climate, transformational